p16 expression in patient with Loop Electrosurgical Excision Procedure (LEEP) - Putu Erika Paskarani; I Gede Sastra Winata; Elisa Laura Oktrinita Sitohang; Felyanto Felyanto; Sang Ayu Putu Yuliantini (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS